Tinjauan Hukum Islam terhadap Hadiah yang Bersumber dari Peserta Perlombaan Bola Voli di Desa Margahayu Selatan Kabupaten Bandung - Muhammad Rayhan Fadhilah; Zaini Abdul Malik; Encep Abdul Rojak (UNISBA Press, 2024)
Abstract. To get rid of the feeling of tiredness and tiredness that people get after working, people need entertainment as a means of refreshing. One of the entertainment that people do as a means of refreshing after work is exercising. Apart from aiming to maintain body health, sport is also often done as a means of competition. Volleyball competitions where there are prizes must be taken into account regarding the status of the prizes, so that there should be no Maisir elements. However, researchers found that the prize money that the competition winners would receive came from the registration fees of the teams participating in the competition. This research aims to find out and understand how volleyball competitions are practiced and understand the Islamic Law review of prizes that come from volleyball competition participants. This type of research is qualitative research using a juridical-normative approach. The data sources used are primary legal materials, secondary legal materials and tertiary legal materials. Data collection used interview, observation, documentation and literature study methods. Then the data obtained is analyzed using qualitative descriptive analysis. The results of the research show that according to Islamic law in volleyball competitions there are discrepancies in terms of awarding competition prize money. Because all the registration money from the participating teams was apparently used by the committee for cash prizes, even though the participants paid the registration money and it was not intended to give prizes to the winners of the competition, the participating teams paid the registration money only as one of the conditions for taking part in the volleyball competition. Abstrak. Untuk menghilangkan rasa lelah dan penat yang didapatkan setelah bekerja manusia membutuhkan hiburan sebagai sarana penyegaran, Salah satu hiburan yang dilakukan oleh masyarakat sebagai sarana penyegaran setelah bekerja adalah berolahraga. Selain bertujuan untuk menjaga kesehatan tubuh, olahraga juga sering dilakukan sebagai sarana kompetisi, Perlombaan bola voli yang terdapat hadiah, harus diperhatikan mengenai status dari hadiah tersebut, jangan sampai terdapat unsur Maisir. Namun, peneliti menemukan bahwa uang hadiah yang akan diterima oleh pemenang perlombaan berasal dari uang pendaftaran tim peserta perlombaan. Penelitian ini bertujuan untuk mengetahui dan memahami bagaimana praktik perlombaan bola voli dan memahami tinjauan Hukum Islam terhadap hadiah yang bersumber dari peserta perlombaan bola voli. Jenis peneltian ini adalah penelitian kualitatif dengan menggunakan pendekatan yuridis-normatif. Sumber data yang digunakan adalah bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier. Pengumpulan data menggunakan metode wawancara, observasi, dokumentasi dan studi pustaka. Kemudian data yang di dapat di analisis menggunakan analisis deskriptif kualitatif. Hasil penelitian menunjukan Tinjauan menurut hukum Islam Perlombaan bola voli ada ketidaksesuaian dari sisi pemberian uang hadiah perlombaan. Karena semua uang pendaftaran tim peserta ternyata digunakan oleh pihak panitia untuk hadiah uang tunai, padahal peserta membayar uang pendaftaran bukan dimaksudkan untuk memberi hadiah kepada pemenang perlombaan, tim peserta membayar uang pendaftaran hanya sebagai salah satu syarat untuk mengikuti perlombaan bola voli.